2013
DOI: 10.1366/13-07086
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Raman Spectroscopy of Whole Hairs

Abstract: This paper describes the application of Raman spectroscopy to whole hair fibers. Previously this has proved difficult because the hairs are relatively opaque, and spatial resolution diminishes with depth because of the change in refractive index. A solution is to couple confocal Raman with multivariate curve resolution (MCR) data analysis, which separates spectral differences with depth despite this reduction in resolution. Initially, it is shown that the cuticle can be separated from the cortex, showing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
(65 reference statements)
1
23
0
1
Order By: Relevance
“…Pudney et al also analyzed bleached hairs from yaks and humans, and showed similar results to Kuzuhara . They demonstrated that for a depth study using both dry and immersion microscope objectives the cuticle region could be distinguished from the cortex, after applying multivariate curve resolution analysis.…”
Section: Trace Evidencementioning
confidence: 80%
“…Pudney et al also analyzed bleached hairs from yaks and humans, and showed similar results to Kuzuhara . They demonstrated that for a depth study using both dry and immersion microscope objectives the cuticle region could be distinguished from the cortex, after applying multivariate curve resolution analysis.…”
Section: Trace Evidencementioning
confidence: 80%
“…The band frequency and FWHM of the six components in the S-S band region are shown in Table I. According to Schlucker et al's method [28], the band frequency of the six components was selected. Here, the band frequency and FWHM of the six components of all hair samples were fixed, as the band intensity of all hair samples was changed.…”
Section: Raman Spectramentioning
confidence: 99%
“…As the work of Frushour and Koenig [8], which provided assignments for the side and main chain vibrations in wool keratin, Raman spectroscopy has been used in structural studies of keratin fibres related to wool finishing [9][10][11][12][13][14][15][16] and hair science [5][6][7][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work using vibrational spectroscopy to study hair structure, such as ATR-FTIR and Raman spectroscopies, provided bulk spectra with some depth profiling of the fibre. 22,23 Chemical microscopies e.g confocal Raman, have been applied to determine chemical variation through the hair fibre using microtome cross-sections. 24 These methods yield relatively poor spatial resolution however, owing to the diffraction limit of light, and thus cannot reveal many crucial sub-micron features of the fibre.…”
Section: Introductionmentioning
confidence: 99%